Pengucapan Alhamdulillah dalam Membina Hubungan Harmonis dalam Rumah Tangga pada Pasangan Muslim - Nurjanis (Jurnal Indragiri Penelitian Multidisiplin, 2025)
The phrase "Alhamdulillah," meaning "Praise be to Allah," holds significant meaning in Islam as an expression of gratitude for blessings and acceptance of divine will. This research explores how the frequent use of this phrase plays a role in fostering harmonious relationships in Muslim marriages. Using a qualitative approach, the study examines how couples incorporate the expression of gratitude into their daily interactions and the impact it has on their relationship dynamics. The findings suggest that regular utterance of "Alhamdulillah" strengthens emotional bonds, promotes positive communication, and enhances mutual understanding, all of which contribute to a peaceful and harmonious marital life. This paper highlights the importance of this spiritual practice as a tool for building lasting harmony in Muslim households.